Dynamics of trapped magnetic flux in superconducting FeTe0.65Se0.35 - Bondarenko, S.I.; Bludov, A.N.; Koverya, V.P.; Link, S.I.; Sivakov, A.G.; Timofeev, V.P.; Gawryluk, D.J.; Puźniak, R.; Wiśniewski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The magnetic moment in the superconducting and normal state of a crystalline FeTe0.65Se0.35 superconductor, grown by the Bridgman’s method with relatively high growth rate, was measured. The temperature and magnetic field dependences of magnetization and its relaxation time were determined. Studied crystal, being non-uniform due to high growth rate of 5 mm/h, exhibits smaller width of superconducting transition in comparison with an ideal crystal grown with velocity of 1 mm/h, and the difference in magnetic properties of crystals grown with various growth rate, related to their microstructure, is discussed.